2009
DOI: 10.1111/j.1467-8535.2009.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Using avatars and virtual environments in learning: What do they have to offer?

Abstract: This paper explores and discusses arguments for the use of virtual environments and interactive avatars in supporting the achievement of student learning goals within conventional educational contexts. It describes and evaluates arguments promoted by some authors (eg, van den Brekel) relating to advantages from gaming and avatar use, ranging from enhanced engagement in learning activities, through to more purposeful and focussed communication, and, when used in group situations, better cooperation and collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 11 publications
1
59
0
4
Order By: Relevance
“…However, we found one in the context of World War II, where students took part in an activity combining the classroom and the D-Day museum via the technology Myartspace (Vavoula et al, 2009). An emphasis on societal issues (sometimes closely related to moral aspects) was in like manner found in the study (Falloon, 2010) of an avatar-based presentation and storytelling tool where the aspects summarised are 'such things as street safety, fighting ethnic prejudice, eliminating tagging, reducing pollution' (p. 117). Actually, quite a few studies refer to a type of multi-perspective possibilities.…”
Section: Virtual Reality In Educationmentioning
confidence: 92%
“…However, we found one in the context of World War II, where students took part in an activity combining the classroom and the D-Day museum via the technology Myartspace (Vavoula et al, 2009). An emphasis on societal issues (sometimes closely related to moral aspects) was in like manner found in the study (Falloon, 2010) of an avatar-based presentation and storytelling tool where the aspects summarised are 'such things as street safety, fighting ethnic prejudice, eliminating tagging, reducing pollution' (p. 117). Actually, quite a few studies refer to a type of multi-perspective possibilities.…”
Section: Virtual Reality In Educationmentioning
confidence: 92%
“…Students worked in groups made up of students of different cultures, in virtual learning environments. Students were asked to create educational tasks in virtual domains, on the assumption that these virtual domains have high learning potential (Campbell, 2009), and that virtual representations affect learning (Falloon, 2010;Hamilton & Nowak, 2010;Resta & Shonfeld, 2013). This research tried to enhance the models and proposals for virtual representations in three-dimensional domains and ascertain their importance to the learner.…”
Section: Discussionmentioning
confidence: 99%
“…There seem to be advantages for learning by using virtual environments and interactive avatars in supporting students' achievement and learning goals within conventional educational contexts, ranging from enhanced engagement in learning activities, to more purposeful and focused communication, and better cooperation and collaboration between students when used in groups (Falloon, 2010;Hamilton & Nowak, 2010;Resta & Shonfeld, 2013). Shonfeld, Resta, and Yaniv (2011) refer to enhancing engagement and social presence by using SL environments.…”
Section: Learning Through Avatarsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive effects on user motivation of entertaining and interactive environments which feature eye-catching objects has been amply demonstrated (Allison, Miller, Sturgeon, Nicoll, & Perera, 2010;Horton, 2000;Sancho, Torrente, & Fernández-Manjón, 2009). Because 3-D virtual worlds possess such objects, those environments are thought to stimulate motivation levels (Falloon, 2010;Iqbal, Kankaanranta, & Neittaanmaki, 2010;Sierra, Gutiérrez, Garzón-Castro, 2012;Zhou, Jin, Vogel, Fang, & Chen, 2011). In the literature, it has also been demonstrated that other features of 3-D environments, such as interactions between users and between individual users and the environment, participation in the provided activities, and the feeling of being truly in the environment (Kapp & Driscoll, 2010) all increase the users' learning capacities (Mishra, 2009).…”
Section: Motivation In 3-d Virtual Worldsmentioning
confidence: 99%